1998
DOI: 10.1002/qj.49712455111
|View full text |Cite
|
Sign up to set email alerts
|

Correction for attenuation of radar reflectivity using polarization data

Abstract: SUMMARKAttenuation by heavy rain is a major operational problem in radar estimation of rainfall rates, and one which is increasingly severe at wavelengths shorter than 10 cm. Gate-by-gate correction algorithms, including those using both reflectivity ( Z H ) and differential reflectivity ( Z D R ) , are inherently unstable. In addition values of ZH and ZDK arc affected by hail, which causes little attenuation. Methods dependent upon differential phase shift (KDP) do not give unique solutions but depend upon ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Therefore, Z DR measurements performed with the antenna pointing at an elevation of 90 o should be 0 dB, and any deviation from that value can be interpreted as the bias of Z DR . However, as we could not manipulate the scan strategy, we followed the suggestion of Smyth and Illingworth (1998) who pointed out that rain drops in regions of light rain were almost spherical and thus Z DR had to be close to zero. Although this approach would not allow for the same precision as the use of a vertically pointing antenna, it appeared reasonable and pragmatic given the expected level of miscalibration.…”
Section: Differential Phase Processingmentioning
confidence: 99%
“…Therefore, Z DR measurements performed with the antenna pointing at an elevation of 90 o should be 0 dB, and any deviation from that value can be interpreted as the bias of Z DR . However, as we could not manipulate the scan strategy, we followed the suggestion of Smyth and Illingworth (1998) who pointed out that rain drops in regions of light rain were almost spherical and thus Z DR had to be close to zero. Although this approach would not allow for the same precision as the use of a vertically pointing antenna, it appeared reasonable and pragmatic given the expected level of miscalibration.…”
Section: Differential Phase Processingmentioning
confidence: 99%
“…One is detection range, whereby the echo power received by the radar will decrease with increasing range, and this applies to all radar wavelengths; the other is rain attenuation. With the exception of intense storms, rain attenuation for electromagnetic waves with a wavelength greater than approximately 7 cm is Illingworth [25] for Z DR correction. One of the advantages of the algorithm is that the coefficient α H of the relationship between A H and K DP is estimated from the radar data rather than scattering simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Bringi et al [8] showed that the specific differential phase K DP can be related to the attenuation A h by means of a power law A h = αK DP , where α is sensitive to the temperature. Both A h and K DP are approximately proportional to the fourth moment of the DSD, and therefore, they are quasi-linearly related [10].…”
Section: Attenuation Correction Techniquesmentioning
confidence: 99%
“…The HB [4] algorithm is given by (7), the Testud et al [11] algorithm (ZPHI) is given by (8), the Bringi et al [12] algorithm (herein referred as BRI) is given by (8)- (10), and the FV algorithm is given by (11).…”
Section: Extended Attenuation Correction Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation